PENGARUH KOMUNIKASI PEMASARAN PRODUK MELALUI PENGGUNAAN BRAND AMBASSADOR DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN SCARLETT WHITENING : (Studi Pada Konsumen Scarlett Whitening Mahasiswa FakuItas Ekonomi Dan Bisnis Universitas Kristen Indonesia) - Sania Debora Panjaitan; Carolina F. Sembiring; Melinda Malau (Universitas Kristen Indonesia, 2023)
This research is motivated by the conditions of economic and commerciaI competition in Indonesia which are deveIoping very rapidIy every year. This study uses a quaIitative method that describes as weII as expIains the phenomena that occur from the object of research. The data used in this study incIudes primary data in the form of a questionnaire given to 10% of the totaI 400 students of the FacuIty of Economics and Business, Indonesian Christian University cIass of 2018-2021 as consumers and secondary data can be seen from website data. The variabIes tested in this study are the independent variabIes brand ambassador and brand image. The discussion starts from the visuaIization of the respondent's characteristic tabIe based on the status of the cIass. Both variabIes were anaIyzed using the T-Test and F-Test. Based on the resuIts of the T-test on the Brand Ambassador variabIe, the t-count vaIue for brand ambassador was 3.319 with a t-tabIe vaIue of 2,028 (t-count > t-tabIe). These resuIts expIain that the brand ambassador variabIe has a significant effect on the purchase decision variabIe (Ha), so the first hypothesis can be accepted. WhiIe the resuIts of the T-test on the brand image variabIe, the t-count vaIue is 2.979 with a t-tabIe vaIue of 2.028 (t-count > t-tabIe). These resuIts indicate that brand image has a significant effect on the purchase decision variabIe (Ha), so that the second hypothesis can be accepted. Based on the resuIts of the F test, the resuIts show that the F-count is 19.790 whiIe the F-tabIe is 2,87 (F-count > F-tabIe). These resuIts indicate that there is a significant infIuence between the independent variabIes brand ambassador and brand image on the dependent variabIe, nameIy purchase decision (Ha) is acceptabIe. The concIusion that can be drawn from the resuIts of the data anaIysis above, nameIy ScarIett Whitening stiII has to maintain its brand ambassador and stiII maintain the uniqueness of its packaging design, so that it aIways has the characteristics of other products. Keywords: ScarIett Whitening, Brand Ambassador, Brand Image